A content analysis of the 'land language' articulated by the political elites concerning South Africa's land question after 2013 : an ideational exploration of an imagined pluralistic security community - Wolmarans, Frederik Gerhardus (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.